How Much Potential Biodiversity and Conservation Value Can a Regenerating Rainforest Provide? A 'Best-Case Scenario' Approach from the Peruvian Amazon. (March 2016) - Whitworth, Andrew; Downie, Roger; von May, Rudolf; Villacampa, Jaime; MacLeod, Ross
The structure and underlying functions of the majority of the world's tropical forests have been disrupted by human impacts, but the potential biodiversity and conservation value of regenerating forests is still debated. One review suggests that on average, regenerating tropical forests hold 57% (±2.6%) of primary forest species richness, raising doubt about a viable second chance to conserve biodiversity through rainforest regeneration. Average values, however, likely underestimate the potential benefit to biodiversity and conservation because they are drawn from many studies of short-term regeneration and studies confounded by ongoing human disturbance. We suggest that the true potential biodiversity and conservation value of regenerating rainforest could be better assessed in the absence of such factors and present a multi-taxa case study of faunal biodiversity in regenerating tropical forest in lowland Amazonia. We found that biodiversity of this regenerating site was higher than might have been expected, reaching 87% (±3.5%) of primary forest alpha diversity and an average of 83% (±6.7) of species estimated to have occurred in the region before disturbance. Further, the regenerating forest held 37 species of special conservation concern, representing 88% of species of highest conservation importance predicted to exist in primary forest from the region. We conclude that this specific regenerating rainforest has high biodiversity and conservation value, and that whilst preserving primary forest is essential, our results suggest that under a best-case scenario of effective conservation management, high levels of biodiversity can return to heavily disturbed tropical forest ecosystems.